Penegakan Hukum Pidana Terhadap Tindak Pidana Pencucian Uang di Bidang Perpajakan - Guntur Rambey (Iuris Studia: Jurnal Kajian Hukum, 2022)
The taxation system always changes from time to time according to the development of society and the state, both in the state and social and economic fields. Tax collection is a form of obligation of citizens as taxpayers as well as an active role to finance various State needs, namely in the form of national development whose implementation is regulated in laws and regulations for the purpose of the welfare of the nation and the State. Assets in the form of money owned as proceeds of crime are generally not directly spent or used by criminals because if they are used directly, law enforcement officers will easily track down the source of the assets obtained. Therefore, the crime of Money Laundering not only threatens the stability and integrity of the economic system and financial system, but can also endanger the foundations of social, national and state life based on Pancasila and the 1945 Constitution of the Republic of Indonesia